Technical Support at the Writing Center - Nguyen, Anna (WritingThreeSixty, 2024)
Background: I am a writing instructor at a local university, where undergraduate students make appointments with me to help with their paper writing. The writing center is a kind of drab smart room that isn’t very smart. The lights are designed to detect motion, but we’re all sitting and staring in front of the computer. The lights turn off in the middle of a discussion. It is rare for a wave of my arm to alert them to flicker back on. The students come to the writing center from various classes. Engineering, literature, public health, art history, science labs, nursing. Some students have drafts, some have outlines, some need guidance to begin. Many of them are overwhelmed, unsure where to start. Others seem guarded or there is an air of defensiveness as they intone the reason why they have made an appointment. When I began my position four months ago, one of my first appointments was with a student from a STEM program. He had an enthusiastic, radio voice, which jolted me from my sedentary slumber on an early Friday morning. He booked an appointment for two hours, on citational formatting. If we had time after the lesson, he would move on to work on small sentence-level edits. Two hours that merely focused on citation seemed excessive, but I followed the student’s goals.